Relasi Syariah Fiqih dan Qonun dalam perspektif Siyasah Syar'iyyah - Muhammad Sya’ban Siregar; Faisar Ananda; M. Iqbal Irham; Nur Asiah (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
This article aims to analyze the relationship between sharia, fiqh, and qanun from a siyāsah syar'iyyah perspective by examining historical practices during the Ottoman Empire and the Mamluk Dynasty. This research uses qualitative methods with a library study approach, drawing on classical and contemporary literature on Islamic law and Islamic political history. The results show that sharia serves as the primary normative source, fiqh as the dynamic interpretation of Islamic scholars, and qanun as an implementable form of codification of state law. From a siyāsah syar'iyyah perspective, these three elements form an integrative and adaptive relationship in responding to societal needs. Studies of the Ottoman period demonstrate a legal dualism between sharia and qanun that developed into a complex legal system, particularly during the Tanzimat period. Meanwhile, during the Mamluk period and the development of law in Egypt, a transformation from the dominance of fiqh to a legal system influenced by modern codification and Western law is evident. Thus, the relationship between sharia, fiqh, and qanun is not static, but rather dynamic and contextual, and oriented toward achieving public welfare as the primary goal of Islamic law.